ATYPICAL DEVELOPMENTAL TRAJECTORIES AND SYMBOLIC ACQUISITION IN CHILDREN WITH ASPERGER SYNDROME. CASE OF CHILDREN AGED 4 TO 8 YEARS IN CAED-CAMEROON - Estelle MEVO NOMO; Adolf MOTE (Universitaria Publishing House, Craiova, 2023)
This contribution repositioned the debate on atypical developmental trajectories and symbolic acquisitions in children with Asperger syndrome. Atypical developmental trajectories are a mode of functioning and structuring governed by attitudes, atypical lines of conduct, gestures and even unconscious reflex movements that are clearly deviated from the developmental stage of the person. In childhood, the awakening of thought and learning in Asperger's syndrome involves a significantly different development. For (Damasio, 1995), individual genetic differences, the effects of age, experience, and especially the emotional factor account for much of the decision making. Data were collected from children with Asperger's Syndrome and their caregivers at the CAED. Analyzed using thematic content analysis, it appears that in ontogenetic development, neurocognitive determinants account for symbolic acquisitions in children with Asperger syndrome. To understand these atypical developmental trajectories, Thomas and Baughman's (2014) neuro-constructivism states that not all cognitive functions are damaged or maladaptive in Asperger syndrome. Furthermore, consideration of the interactive specialization of theories of cognition must be constrained by experimental data. Thus, the developmental atypicalities of children with Asperger's Syndrome are driven by the desire to open up to the world, to solve problems in a timely manner, hence the symbolic acquisition of retro and systemic proactivity.